2020
DOI: 10.1111/hex.13064
|View full text |Cite|
|
Sign up to set email alerts
|

Utilizing patient advocates in Parkinson’s disease: A proposed framework for patient engagement and the modern metrics that can determine its success

Abstract: The wide application of patient engagement and its associated benefits has increased across government, academic and pharmaceutical research. However, neither an identified standard practice for the process of engagement, nor utilization of common metrics to assess associated outcomes, exists. Parkinson's Foundation developed a patient engagement framework and metrics to assess engagement within the academic research and drug development sectors. This approach was developed over the course of several years thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 18 publications
(37 reference statements)
1
14
0
Order By: Relevance
“…They express a strong desire for information and anticipatory guidance regarding PDP and indicated that they obtained most information from non-physician sources. This reinforces the important role that formal and informal social and support networks may have for individuals with neurologic disorders and their families, including support groups, patient advocacy groups, and foundations (16). Interestingly, the most common free-text peer advice category was to alert the care recipient's neurologist.…”
Section: Discussionmentioning
confidence: 67%
“…They express a strong desire for information and anticipatory guidance regarding PDP and indicated that they obtained most information from non-physician sources. This reinforces the important role that formal and informal social and support networks may have for individuals with neurologic disorders and their families, including support groups, patient advocacy groups, and foundations (16). Interestingly, the most common free-text peer advice category was to alert the care recipient's neurologist.…”
Section: Discussionmentioning
confidence: 67%
“…Whilst we found the work described by Feeney et al 1 interesting, we nonetheless have some serious reservations and feel that the paper reflects some long‐standing biases in the medical field that have held patient engagement back.…”
mentioning
confidence: 79%
“…We read with interest the recent article by Feeney and colleagues on ‘utilizing (sic) patient advocates in Parkinson's disease’ 1 . We acknowledge that sound methods for patient engagement need to be developed and evaluated.…”
mentioning
confidence: 99%
“…Feedback was provided to all parties in the research project and publicly discussed whether PPI was executed with success. This framework may serve as a model for other PPI networks to emulate, in order to standardize research practice to include and report on patient engagement 9 …”
mentioning
confidence: 99%